The Constitutional Right to Life versus the Right to Dignity: A legal analysis of whether euthanasia should be legalised in South Africa - Ameer, Omayya (The IIE, 2022)
Euthanasia frees anyone suffering by enabling them to experience a gentle death.1 S v Makwanyane2 pointed out that ‘the Right to Life includes the Right to Dignity emphasizing that the Right to Life and the Right to Dignity are entwined.’3 Human dignity must support the Right to Life and should not be excluded.4 In euthanasia there is a clash as the Right to Life shield’s life and the Right to Dignity favours death of persons.5 My research will discover whether euthanasia should be legalised in South Africa when it uncovers which right will triumph between the Right the Life and the Right to Dignity regarding euthanasia. Euthanasia is frequently illegal but countries like the Netherlands, Canada and Belgium allows euthanasia meaning no prosecution happens if the doctor had followed specific procedures in law.6 The Constitution of the Republic of South Africa 1996,7 also allows sustaining treatment to be withdrawn however euthanasia is still regarded as murder by many.8 There are positive and negative aspects to euthanasia.9 Euthanasia goes against the Islamic and Christian religion and weakens sanctity of life.10 It constitutes as a threat to values of society.11 The common law says that if anyone participates in euthanasia, they ‘’will be guilty of murder or culpable homicide’’.12 Euthanasia greatly affects terminally ill patients inside South Africa considering that it is a perfect solution to end their suffering.13 The South African Law Commission did submit their report called Euthanasia and the Artificial Preservation of Life (project 86), which tries to assist terminally ill patients, but it has been completely ignored as remains in limbo.14 Euthanasia is regarded as a humane when it’s applied to animals but not humans.15 The Constitution should consider legalizing euthanasia to serve terminally ill patients that are suffering.16 Preserving that life of a terminally ill patient extends their pain because it forces them into an undignified death.17
Keywords: Constitution; Euthanasia; South Africa